Mystery : an Alex Delaware novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2011)
Psychologist Alex Delaware and his girlfriend Robin are making a farewell visit to an LA hotel bar when one patron in particular grabs their attention -- a beautiful but aloof young woman dressed all in white. Two days later, Alex is called in on a murder case and is shocked when he recognizes the victim as the woman in white.